2007
DOI: 10.1038/modpathol.3800737
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and viral load of eight oncogenic types of human papillomavirus (HPV) and HPV 16 integration status in cervical intraepithelial neoplasia and carcinoma

Abstract: Current human papillomavirus (HPV) DNA testing using pooled probes, although sensitive, lacks specificity in predicting the risk of high-grade cervical intraepithelial neoplasia (CIN 2/3) progression. To evaluate selected HPV genotyping, viral load, and viral integration status as potential predictive markers for CIN progression, we performed HPV genotyping in formalin-fixed, paraffin-embedded cervical tissue with cervical carcinoma (29 cases) and CINs (CIN 1, 27 cases; CIN 2, 28 cases; CIN 3, 33 cases). Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 57 publications
8
48
0
1
Order By: Relevance
“…Inform HPV III probe sets able to detect 13 types of oncogenic HPV (i.e., types 16,18,31,33,35,45, 51, 52, 56, 58, 59, 68, and 70) were provided by Ventana Medical Systems. The ISH assay was performed according to the manufacturer's guidelines using the BenchMark automated slide staining system (Ventana Medical System).…”
Section: Thementioning
confidence: 99%
“…Inform HPV III probe sets able to detect 13 types of oncogenic HPV (i.e., types 16,18,31,33,35,45, 51, 52, 56, 58, 59, 68, and 70) were provided by Ventana Medical Systems. The ISH assay was performed according to the manufacturer's guidelines using the BenchMark automated slide staining system (Ventana Medical System).…”
Section: Thementioning
confidence: 99%
“…Epidemiology studies and our previous observations in cervical tissue specimens demonstrated that the eight major oncogenic HPV types, HPV16, 18, 31, 33, 35, 45, 52 and 58, are closely associated with CIN 2/3 and cervical carcinoma, collectively accounting for more than 80% of cervical carcinoma and CIN 2/3. [10][11][12] Of these eight types, HPV16 and 18 are the most clinically relevant HPV types. 10,21 In our study using Pap cytology specimens, we confirmed that HPV16 and 18 had the highest association with CIN 2/3/carcinoma in women with LSIL or ASCUS.…”
Section: Discussionmentioning
confidence: 99%
“…15 HPV DNA was determined using consensus primer-mediated PCR assays as described previously. 12 Briefly, b-globin (268 bp) was amplified to determine the quality of the extracted DNA using primer sets pc04/gh20 according to Bauer et al 16 and using AmpliTaq Gold polymerase (Applied Biosystems, Foster City, CA, USA). A 25-ng aliquot of genomic DNA was added to a PCR master mixture containing 1 Â PCR buffer (100 mM Tris-HCl, 500 mM KCl, pH 8.3), 200 mM concentrations of each deoxynucleoside triphosphate, 200 nM primer, 1.5 mM MgCl 2 , and 2.5 units of AmpliTaq Gold DNA polymerase.…”
Section: Hpv Dna Testing Using Consensus Primer-mediated Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…For now, it remains largely unclear whether the measurement of HPV integration status could be a useful biomarker for progressive disease. Several studies suggest that identification of integrated viral forms could support HPVbased screening and triage strategies (2,(69)(70)(71)(72)(73)(74)(75).…”
Section: Hpv Analysis: Possibilities and Methodsmentioning
confidence: 99%